Analysis of Causes of Fleet Delays to Stuffing Locations (On Time Pick-Up) Using the Root Cause Analysis (RCA) Method (Case Study of Logistics Company in Surabaya) - Purba, Ari Pranata Primisa; Salsabila, Selvin; Zahrina, Nadhilah (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2025)
PT ABC Logistics is a company engaged in logistics services, especially providing truck and container services for land transportation. This company operates various types of trucks, including 20 feet, 40 feet, 21 feet, CDD, CDE, Fuso, and Tronton trucks. In carrying out its operations, as a logistics company, it must plan fleet needs accurately to fulfill each order. However, problems are still found in the form of fleet delays when heading to the stuffing location to the customer. To overcome this problem, the Root Cause Analysis (RCA) method is used to identify the root of the problem and reduce potential delays. The approaches applied include the use of Pareto Diagrams, Fishbone Diagrams, Failure Mode and Effect Analysis (FMEA), and proposing improvements using the 5W + 1H method. The results of the analysis show two main factors causing delays, namely fleet wait and container shortage. Priority improvements for fleet wait include optimizing route plans that have not been updated, incompatibility between delivery times and slot times, and lack of communication between the company and vendors. Meanwhile, to overcome delays due to container shortages, the focus of improvements is focused on improving communication systems, repairing damaged containers (such as leaks or holes), and optimizing communication between vendors and companies.